Hubungan Status Gizi dengan Pola Makan Siswa Kelas IIIC SDN 064981 Cempaka Raya - Sudana Fatahillah Pasaribu; Tuty Hertati Purba; Diana Reminiscere Telaumbanua; Hizkia Aribona Sianturi; Uski Sasja Rahmadani; Ludhovika Renata (STIKes Ibnu Sina Ajibarang, 2025)
The nutritional status of elementary school-aged children is an important indicator in assessing health conditions, quality of life, and supporting optimal growth and development. School-aged children are in an active growth phase and therefore require a balanced nutritional intake to support learning activities, physical development, and cognitive abilities. This study aims to determine the relationship between nutritional status and dietary patterns in grade III C students of SD Negeri 064981 Cempaka Raya in 2025. This study used a quantitative approach with a cross-sectional design that allows researchers to assess the relationship between variables at a specific time. The study population consisted of all grade III C students, with a sample size of 30 students determined using a total sampling technique. Data on nutritional status were obtained through anthropometric measurements using the Body Mass Index for Age (BMI/U) referring to WHO standards. Meanwhile, dietary data were collected through a food frequency questionnaire that included the type, frequency, and daily food consumption habits of students. Data analysis was carried out using the Chi-Square test to examine the relationship between dietary patterns and nutritional status. The results showed a significant relationship between dietary patterns and students' nutritional status (p < 0.05). This indicates that a regular, balanced diet that meets energy needs plays a crucial role in establishing good nutritional status in elementary school children. These findings underscore the importance of schools in providing nutrition education, as well as the role of parents in fostering healthy eating habits within the family. Therefore, collaborative efforts to foster appropriate eating behaviors are essential to support children's physical growth, cognitive development, and ongoing academic achievement.